Faktor Representasi Seni Bondres Persfektif Etika Hindu - Nyoman Suardika; I Wayan Sunampan Putra (Jayapangus Press, 2021)
Art is one of the elements of culture that is well known in Balinese life. One of the arts in Balinese society is bondres art. Bondres art is a folk entertainment art that is thick with elements of humor but is also inseparable from ethical values. However, with its development, bondres art continues to develop by giving birth to representations that are basically influenced by several factors. The purpose of this study is to explain the factors that influence the representation of Bondres art in the city of Singaraja. The research method uses qualitative data types with a theoretical approach to social practice. Data was collected by several data collection methods then analyzed and presented with qualitative descriptive. The results of this study are several factors that influence the representation of Bondres art including; 1) Creativity factor, namely the ability of artists to create bondres art forms, 2) Education and knowledge factors, namely capital in the form of the abilities possessed by artists in creating bondres art, 3) Community social factors, namely the influence of the community that supports artists in creating bondres art, 4 ) Globalization factor, namely the influence of globalization which includes technology, modernization of artists to form representations. All of these are factors that influence the representation of Bondres art in the city of Singaraja.